An Utilization Of Solid And Liquid Waste From Palm Oil As A Power Plant - Dimas Apriangga; Dina Tambubolon; Ermando Sihombing; Evifany Prilia Siregar; Solly Aryza (Sean Institute, 2024)
The utilization of solid and liquid palm oil waste as a renewable energy source for electricity generation is an effort to address waste management issues while improving energy efficiency. This study aims to analyze the potential of palm oil waste, including empty fruit bunches, fibers, shells, and liquid waste (Palm Oil Mill Effluent - POME), in generating electricity through suitable power generation technologies. The methodology includes data collection on the quantity and characteristics of palm oil waste, calculation of the energy potential, and evaluation of energy conversion technologies such as direct combustion, gasification, and biogas production from liquid waste. The study also exam-ines the technical and economic feasibility of implementing palm oil waste-based power plants. The results indicate that solid and liquid palm oil waste has significant energy potential. Empty fruit bunches and shells can generate energy through combustion, while liquid waste produces biogas with high methane content through anaerobic pro-cesses. With optimal management, palm oil waste can provide a reliable source of elec-tricity, reduce dependency on fossil fuels, and support environmental sustainability. This study concludes that utilizing palm oil waste for electricity generation not only enhances energy efficiency but also delivers economic and environmental benefits. Further imple-mentation requires policy support, appropriate technology, and sustainable waste man-agement practices by the palm oil industry.